Covid-19 and government decisions about the reopening of educational institutions in a particular school in Distrito Federal: a school psychology report (Research, Society and Development, 2021)
The article discusses the return face students from Kindergarten and Elementary Education I, a private school system amid the pandemic Covid-19. Actions supported by the government of Distrito Federal were analyzed, as also the reality of families in a private school, seeking to identify factors that influenced the position of those responsible, in order to allow the return of their children during the reopening of educational educations. The methodological investigation was through experience report, comparing the analysis of satisfaction questionnaires sent to families about the online classes and direct surveys, with the sole intention of knowing the number of families interested in the face-to-face return, and associating these analyzes  with different decrees, all published in DODF. Concomitantly, there is bibliographic support in relation to the school scenario, thus presenting other experiences lived during the pandemic. After analysis, the discussion followed a chronological line of thought, initially debating on distance education, bringing its various challenges, both from the bibliographic perspective and from the perspective of the Psychology Team of the school in question. In a second moment, it was discussed the change in the perspective of those responsible, in relation to the face-to-face return, with the government decisions of the moment, despite the rise of the Covid-19 cases. It is concluded that the Covid-19 pandemic determined, in some way, a moment of teachers' resilience and creativity, at the same time that it caused emotional distress in the school community, also reflecting on the social inequalities between public and private schools.